2023
DOI: 10.4062/biomolther.2023.132
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Signaling Pathways in Tumor Progression

Abstract: Many cancers arise from sites of chronic inflammation, which creates an inflammatory microenvironment surrounding the tumor. Inflammatory substances secreted by cells in the inflammatory environment can induce the proliferation and survival of cancer cells, thereby promoting cancer metastasis and angiogenesis. Therefore, it is important to identify the role of inflammatory factors in cancer progression. This review summarizes the signaling pathways and roles of C-reactive protein (CRP) in various cancer types,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 143 publications
0
5
0
Order By: Relevance
“…In this study we showed that pre-incubation with the FAK inhibitor I (CAS 4506-66-5 VWR) for 24 h prior to treatment with mCRP abrogated the U937 aggregation, indicating a FAK-dependent mechanism. Previous studies have demonstrated that CRP binding through α2β1 integrins activated FAK, and subsequently MAP kinase pathways, resulting in increased breast cancer cells adhesion and invasion [ 18 ]. In macrophages, FAK modulation is known to be critical for initiation and perpetuation of adhesion and motility, and although interactions through integrin activation predispose macrophage to M1 phenotypical polarization, our study is the first to show a direct link between mCRP, FAK, and monocyte aggregation, and subsequent polarization to the pro-inflammatory phenotype [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study we showed that pre-incubation with the FAK inhibitor I (CAS 4506-66-5 VWR) for 24 h prior to treatment with mCRP abrogated the U937 aggregation, indicating a FAK-dependent mechanism. Previous studies have demonstrated that CRP binding through α2β1 integrins activated FAK, and subsequently MAP kinase pathways, resulting in increased breast cancer cells adhesion and invasion [ 18 ]. In macrophages, FAK modulation is known to be critical for initiation and perpetuation of adhesion and motility, and although interactions through integrin activation predispose macrophage to M1 phenotypical polarization, our study is the first to show a direct link between mCRP, FAK, and monocyte aggregation, and subsequent polarization to the pro-inflammatory phenotype [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is an acute-phase protein synthesized by the liver in response to inflammatory stimuli. It exerts pro-inflammatory responses that are associated with tumour invasion and plays a role in promoting tumour immune escape [51].…”
Section: Non-specific Biomarkers Of Inflammation (Crp Ldh and Esr)mentioning
confidence: 99%
“…CRP can bind to a variety of exogenous and endogenous ligands that are exposed on the cell membrane in the presence of damage, necrosis or apoptotic cells. CRP strongly activates the classical complement pathway which further amplifies tissue damage and potentially makes the disease more severe [41].…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 99%
“…CRP interacting with TLRs leads to signaling pathways that increase the production of pro-inflammatory cytokines including TNF-α, IL-1, and IL-6 in macrophages and monocytes. These cytokines cause further tumor growth, angiogenesis, tumor cell survival, proliferation, and tumor cell resistance to apoptosis [41]. This process will trigger further cancer progression and metastasis, and indirectly affect the increase and worsening of patient symptoms and complaints and may risk contributing to reducing the quality of life of lung cancer patients.…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 99%